Piloting a Simulated Electronic Health Record in Cambodia for Nursing Students in a Nursing Informatics Course. - MAO, Eam; HESTER, Tricia; TUN, Sreypeov; SOUN, Monirath; PARKER, Cheryl D. (Singapore Nursing Journal)
Introduction Electronic health records (EHR) integration is vital in modern healthcare, yet there is limited research on EHR training in nursing education in Cambodia and the ASEAN region. This study explores the implementation of simulated EHR training for Cambodian nursing students and its potential benefits for the curriculum. Method A four-week pilot was conducted with 62 Cambodian nursing students at the University of Puthisastra. Students participated in simulated EHR activities and completed a post-course survey to identify challenges such as medical terminology, computer literacy, and English proficiency. Results 93.5% of students recommended continuing EHR training despite challenges, including difficulties with medical terminology (43.5%), computer literacy (40.3%), and English proficiency (32.3%). Students acknowledged the importance of EHR in improving healthcare delivery. Discussion While students faced language and technical barriers, simulated EHR exposure provided valuable experience. Localising resources and enhancing medical terminology training could improve EHR education. This study contributes to the literature on EHR training in Cambodia and the ASEAN region, suggesting the need for curriculum and technology development.